Hindu wife, Hindu nation : community, religion, and cultural nationalism - Sarkar, Tanika (New Delhi : Permanent Black ; Bangalore : Distributed by Orient Longman, 2001)
Study with special reference to Bengal (India).
Keywords: Hindu women -- Social conditions; Hindu women -- Government policy -- India; Women in popular culture -- India; Women in Hinduism -- India; Hinduism and politics -- India; India -- Politics and government; India -- Religious life and customs